TRANSFER PENGETAHUAN DAN KETERAMPILAN PUBLIC SPEAKING DI LEMBAGA KURSUS PELATIHAN KITA CENTER KOTA PEKANBARU - Nurkhoiriah, Nurkhoiriah; Sumardi, Sumardi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: this study examined the skills of speaking in front of the multitude that is commonly called public speaking by using technical and english-speaking techniques and arts in public so that it makes speech less boring and the intent and purpose of the talk can be conveyed well. The purpose of this study is to learn the training activities we center in moving, moving or transferring skills in public speaking (public speaking) by using the knowledge transfer learning strategy. This type of research is a naturalistic descriptive approach with a qualitative process of data collecting done by interviewing the 3 research subjects of 1 core informant and 2 control informants with the accompanying documentation. Based on interviews researchers came up with three indicators of this: (1) the process of the movement of knowledge, (2) the learning process, (3) the transfer of knowledge. The study of the 3rd indicator is helpful in understanding how the appropriate forms and stages of using the transfer of knowledge on the training process were to lower and transfer public speaking skills toward others so that others could have such desired and required speaking skills.Key Words: Transfer Of Knowledge, Skills, Public Speaking